A low pass filter based integrator in a digital feedback loop AGC for WLAN receivers - H P, Bharath; I Basarkod, P (International Journal of Engineering and Technology, 2018)
This paper describes a Digital feedback loop automatic gain control (AGC) for Wireless Local Area Network (WLAN) receivers. The proposed AGC employs a novel lowpass filter-based integrator for the gain generation, which controls digital multiplier to maintain constant signal dynamic range. The AGC performance is analyzed for 16 and 64 Quadra-ture Amplitude Multiplexing-Orthogonal Frequency Division Multiplexing (QAM-OFDM) modulated signal with differ-ent attenuation factors under Additive White Gaussian Noise (AWGN) channel. The proposed AGC has a dynamic range of 70dB with the gain error less than ±1dB and settling time is 1.2µs. The proposed algorithm is validated on a Field Programmable Gate Array (FPGA) platform.